Isolation and Characterization of Rapid Cellulose Degrading Fungal Pathogens from Compost of Agro Wastes - Makeshkumar, V. (International Journal of Pharmaceutical & Biological Archive, 2012)
ABSTRACT Cellulose is the most abundant biopolymer renewable natural product in the biosphere. Cellulose degrading fungal pathogens play an important role in the biosphere by recycling cellulose mediated by cellulase enzyme and common in field such as forest soils, in manure and on decaying plant tissues. This present study was focused on the isolation, identification and strain improvement of cellulose degrading fungus from compost of agro wastes. 0.1 g of compost samples from 10-3 and 10-4 serially diluted and cultured on Rose Bengal Agar medium (RBA) enriched with 1% Carboxy Methyl Cellulose(CMC) as sole source of carbon. Cellulose degrading fungal pathogens were identified by standard phenotypic method. Isolated cellulose degrading fungal pathogens were subjected with UV-irradiation method at different times of intervals. All exposed RBA with 1% CMC plates were incubated at maximum period and observed fungal growth pattern. Strongly UV resistant cellulose degrading fungal mutant strain and wild strain was evaluated and confirmed by reducing sugar property method. From this study, six pure potential cellulose degrading fungal pathogens (i.e., Fusarium sp., Aspergillus fumigatus, Cladosporium sp., Aspergillus flavus, Pyricularia sp. and Nigrospora sp.) were isolated. Out of six UV exposed strains of cellulose degrading fungus, Fusarium genus only showed excellent growth at 5th day of incubation at different time of intervals. While other five strains of cellulose degrading fungus were showed no growth at maximum period of incubation. This study was concluded that the mutant strain of Fusarium genus was considered as an effective strain for cellulose degradation. Hence it was suggested that, this mutant strain could be exploited for composting of various organic wastes.